Development of Muar Driving Cycle Based on Real-World Driving Conditions - Shafiruddin, Nur Syamin Ikhmal; Che Wan Haimai, Che Wan Mohd Naim; Zainal Abidin, Shaiful Fadzil (Progress in Engineering Application and Technology, 2022)
A driving cycle is a graph that represents vehicle speed over time of aspecific area and characterizes a typical driving pattern for a city's population atdifferent driving conditions such as peak and off-peak. This research aims to designand develop Muar Driving Cycle (MDC) based on the actual driving condition.Selection of routes made via Google Traffic based on the congestion level and drivingconditions for urban, semi-urban and rural areas in the Muar district. The data wascollected using the test vehicle Proton Saga 1.3L CVT, equipped with the data loggersystem. Recording data has been segregated according to the maximum vehicle speedfor each micro-trip. Micro-trips were combined to construct the Muar Driving Cyclebased on target speed and acceleration. The initial driving pattern of MDC has beendeveloped and the cycle characteristic are presented. The results obtained arecompared with the current driving cycle including NEDC, WLTC and the MUDC.MDC has the high velocity with an average of 40.66 km/h with a maximum speed of112.06 km/h and average acceleration of 0.263 m/s2 . The drive cycle should bevalidated through vehicle simulation and the chassis emission cycle test in the future.The findings from the study would benefit in identifying the optimum solution forpowertrain and vehicle technologies for Malaysian driving conditions.